2012
DOI: 10.5620/eht.2012.27.e2012020
|View full text |Cite
|
Sign up to set email alerts
|

Association between Household Income and Asthma Symptoms among Elementary School Children in Seoul

Abstract: ObjectivesThis study examined the association between socioeconomic factors and asthma symptoms.MethodsA total of 6,919 elementary school children in Seoul were enrolled in the study. Data were obtained from a web-based questionnaire survey. The questionnaire was based on the International Study of Asthma and Allergies in Childhood core module. The prevalence of wheeze in the past 12 months and severe asthma symptoms were obtained. The potential risk factors for asthma symptoms included household income and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
3
3
0
1
Order By: Relevance
“…A review by Mielck et al demonstrated conflicting results concerning the association between socioeconomic status and childhood asthma, but revealed that socioeconomic disadvantage is associated with increased risk of asthma [38] . Our study results are consistent with previous studies reporting associations of socioeconomic and sociodemographic factors with wheezing or asthma in age groups varying from the preschool period until adolescence [6] – [12] , [23] . The finding of a decreased risk on wheezing in other Western children, compared to Dutch children, might be partly attributable to a ‘healthy migrant’ effect, in the case that healthy first-generation immigrants who decided to come to the Netherlands for work were on average healthier than the native-born [20] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A review by Mielck et al demonstrated conflicting results concerning the association between socioeconomic status and childhood asthma, but revealed that socioeconomic disadvantage is associated with increased risk of asthma [38] . Our study results are consistent with previous studies reporting associations of socioeconomic and sociodemographic factors with wheezing or asthma in age groups varying from the preschool period until adolescence [6] – [12] , [23] . The finding of a decreased risk on wheezing in other Western children, compared to Dutch children, might be partly attributable to a ‘healthy migrant’ effect, in the case that healthy first-generation immigrants who decided to come to the Netherlands for work were on average healthier than the native-born [20] .…”
Section: Discussionsupporting
confidence: 93%
“…Wide variations exist in the symptom prevalence of childhood asthma worldwide, with a general trend of higher asthma prevalence in more affluent countries [5] . Some studies report that asthma prevalence is disproportionately high among socially disadvantaged children [6] – [12] others found no or only a weak association between social disadvantage and childhood asthma [13] – [17] . Also variations in the prevalence of asthma and asthma-like symptoms were found among children with different ethnic background living in the same country [18] [23] .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic and socioeconomic factors were related to the incidence of childhood asthma in this study, similar to previous studies in Korea [18,19]. Socioeconomic factors relate to both the surrounding environment and the residential or indoor environment.…”
Section: Discussionsupporting
confidence: 89%
“… 1 , 2 There are significant disparities in asthma control status among children with different SES, with those from lower SES having poorer asthma control compared with children from higher SES. 3 , 4 Despite the influence of SES on health outcomes, common measures of SES are difficult to obtain in routinely used data sources for clinical research such as administrative data sets and medical records. 5–7 SES measures at an aggregate level (e.g., census tract, block-group or zip code) are used as proxy measures for individual SES.…”
Section: Introductionmentioning
confidence: 99%